The synergy between leadership, work regime, and quality-of-life - José, Vasco; Palma-Moreira, Ana; Au-Yong-Oliveira, Manuel (Frontiers in Psychology, 2025)
IntroductionThe primary objective of this research was to investigate the relationship between leadership and quality of life and whether this association is moderated by the work regime (remote, hybrid, or in-person). Additionally, we aimed to investigate the relationship between work regime and quality of life, as well as the mediating effect of leadership on this relationship.MethodsA total of 231 individuals working under different work regimes (in-person, hybrid and remote) participated in this study. This study followed a quantitative methodology.ResultsLeadership has a positive and significant association with the perception of quality-of-life. The work regime has a significant effect on the perception of quality-of-life and moderates the relationship between transformational leadership and the perception of quality-of-life. The work regime has a significant impact on the perception of leadership. Leadership has a mediating effect on the relationship between the work regime and the perception of quality of life.DiscussionThis study demonstrates that technology can be an ally in increasing individual well-being, provided it is accompanied by effective leadership practices tailored to the adopted regime. Employees’ perception of quality of life emerges not only because of the conditions adopted, but also from a synergy involving the context (work regime) and management capable of leading in a manner appropriate to the remote or hybrid context.